Consumer Segmentation of Protein Diet Based on Gender Differences - Rakesh Achanta, Dr. Preetha Menon (International Journal of Advanced Science and Technology, 2020)
Proteins are an important component of the development of human health. Different types of proteins can be derived from various food products to aid a healthy lifestyle. Protein needs highly differ between males and females with both genders show differing tendencies to their needs. The objective of this paper is to analyze the awareness and protein needs among both the genders on four main attributes i) Diet Doesn’t meet protein needs ii) Want to increase protein intake iii) Additional Dietary supplement iv) Social media following. Data collection methods comprise qualitative methods like Online Surveys, House calls. Statistical Analysis i.e. Independent Two-Sample T-Test has been conducted on the data to understand the significant differences among both the genders for the aforementioned attributes. It has been proved that both males and females showed a significant difference and much aware of their protein needs to lead a healthy lifestyle. Three consumer cohorts have been defined on analyzing the dataset i) The Contended Conservative ii) The Flamboyant Explorer iii) The Traditional Modernist, which can ease the marketer's efforts and resources by targeting these consumer segments.